Lessons and Legacies X : back to the sources ; reexamining perpetrators, victims, and bystanders - Horowitz, Sara R. 1951-; Lessons and Legacies Conference on the Holocaust (Northwestern University Press, 2012)
Foreword / Theodore Zev Weiss -- Introduction / Sara R. Horowitz -- I. Wartime sources of interpretation -- Another look at Hitler and the beginning of the Holocaust / Gerhard L. Weinberg -- Police force under occupation: Serbian State Guard and volunteers' corps in the Holocaust / Ana Antić -- Jewish mystical thought (Kabbalah) through the Holocaust / Gershon Greenberg -- "Realism"? the place of images in Holocaust studies / Paul B. Jaskot -- II. Rethinking testimony -- Collaborative interpretation of survivors' accounts: a radical challenge to conventional practice / Henry Greenspan -- Incapable of revealing the event: Elie Wiesel and the reading of memoir-writing / Gary Weissman -- III. Victimhood, identity, practice -- Political upheaval and shifting identities: Holocaust survivors in the Soviet Occupied Zone of Germany, 1945-1949 / Cora Granata -- The aftermath and after: memories of child survivors of the Holocaust / Joanna Beata Michlic -- From Nuremberg to Kigali: on the necessity and impossibility of post-atrocity justice / Valerie Hébert -- IV. Art -- Reflections, traditions, and representations from a painting studio / Matthew Girson